Workers’ Psychological Distress During the Early Months of the COVID-19 Pandemic in Brazil: A Cross-Sectional Study - Alonso, Melissa Spröesser [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Dias, Adriano [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Ruiz-Frutos, Carlos; Fagundo-Rivera, Javier; Gómez-Salgado, Juan; Bernardes, João Marcos [UNESP] (MDPI, 2025)
The COVID-19 pandemic significantly impacted the mental health of workers. This study aimed to assess the prevalence of psychological distress among Brazilian workers during the early months of the pandemic and explore its associated factors. A cross-sectional study was conducted using an online questionnaire administered to 2903 Brazilian workers, including 1752 non-healthcare workers (NHCWs) and 1151 healthcare workers (HCWs), between April and May 2020. Snowball sampling was employed for participant recruitment, and the research questionnaire was adapted for use with the Brazilian population through a process of translation and cultural adaptation, based on an instrument initially created and validated for use in Spain. Differences between NHCWs and HCWs were tested using the chi-square or Fisher’s Exact test and Mann–Whitney test followed by effect size measurement. Multiple linear regression models were used to analyze the association between psychological distress and the predictor variables. Psychological distress was observed in 72.6% (95% CI 70.1–74.2%) of the participants, with no significant difference observed between NHCWs and HCWs. Although 32 variables showed statistically significant differences between NHCWs and HCWs, only 7 demonstrated clinical–epidemiological relevance, primarily related to occupational factors. Work-related stress was positively associated with psychological distress, but this relationship diminished in the absence of family members infected with COVID-19. Conversely, a higher sense of coherence was protective against psychological distress, although this effect weakened in the absence of family members infected with COVID-19. The study highlights the high prevalence of psychological distress among Brazilian workers during the pandemic’s early months. Work stress played a significant role, while sense of coherence appeared to mitigate mental health challenges. These findings highlight the need for targeted mental health interventions, particularly for workers facing both professional and family-related stressors during crises.
Keywords: COVID-19; epidemiology; mental health; preventive medicine; psychological distress; socioeconomic aspects of health